The Management of Mae Malai Fresh Market in Khilek Subdistrict, Mae Taeng District, Chiang Mai Province: The Management of Mae Malai Fresh Market in Khilek Subdistrict, Mae Taeng District, Chiang Mai Province - jaimoon, kanitta; Tantra, Thammaporn; Techatunminasakul, Suriyajaras (RATANABUTH JOURNAL, 2026)
This research article aimed to study: 1) the history and development of Mae Malai Fresh Market; 2) the management of Mae Malai Fresh Market; and 3) appropriate approaches for the sustainable management of Mae Malai Fresh Market. This study employed a qualitative research approach. Data were collected from 56 key informants, including market committee members, community leaders, vendors, and consumers, through in-depth interviews. The data were analyzed using content analysis. The findings revealed that Mae Malai Fresh Market was established in response to the community’s need for a place to exchange goods and conduct business, and it has gradually developed into an important economic center of the area. The market is managed through a community participatory approach, in which the market committee is responsible for establishing regulations, allocating trading spaces, maintaining public utilities, and coordinating with local government agencies. The study also found that the effectiveness of market management depends on three key factors: the capacity of the market committee, the participation of vendors and community members, and support from local government agencies. Therefore, sustainable management of Mae Malai Fresh Market should focus on strengthening the capacity of the market committee, promoting the participation of all stakeholders, and improving the management system in accordance with the local community context. These efforts will enable the market to continue serving as a local economic center and contribute to strengthening the community in the long term.